SWOT Analysis of the READSI Program in North Luwu: Assessing Effectiveness and Introducing the SIFITRI Strategy - Amir, Fitriani; Akib, Haedar; Nur, Andi Cudai (Journal of Management World, 2025)
In many developing countries, rural communities often face significant challenges  that hindering agricultural productivity and economic growth. These challenges include limited access to resources, lack of training, inadequate infrastructure, and resistance to adopting new technologies. This study assesses the implementation of the Rural Empowerment and Agricultural Development Scaling-up Initiative (READSI) program in North Luwu Regency, focusing on its efficacy in enhancing farmers' welfare. The objective was to evaluate how well the program has improved agricultural productivity and incomes. The study employed a qualitative case study methodology, collecting data  through in-depth interviews with program participants, agricultural extension officers, and other pertinent stakeholders. Thematic analysis was utilized to identify recurring themes and patterns, while descriptive statistics summarized the demographic information of the interviewees. The results revealed that READSI has significantly increased agricultural productivity and farmers' incomes by providing targeted training and improved access to agricultural inputs and technology. However, challenges such as infrastructural deficiencies, resistance to adopting new technologies, and human resource constraints persist. The findings contribute to the literature on rural development and offer practical policy recommendations for enhancing similar initiatives. Implementing the SIFITRI strategy could significantly bolster the resilience and sustainability of rural development programs, ensuring continuous improvement in farmers' welfare.